Testing for feedback-conditional regret effects using a natural lottery - Steven J. Humphrey; Paul Mann; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2005)
We report the results of an experimental test for feedback-conditional regret effects using a naturally occurring gamble. The properties of this gamble are likely to engage decision-makers to a greater extent than conventional abstract laboratory gambles, and be more generally exhibited by real world objects of choice. We argue that this conveys a higher than typical degree of external validity on our findings. We observe that feedback on the outcome of foregone choices enhances the salience of regret as a decision motive.
Keywords: D81; C91; 330; regret theory; outcome feedback; natural lottery; external validity; Entscheidungstheorie; Risiko; Spieltheorie